HUBUNGAN TEKANAN KELUARGA TERHADAP KESEHATAN MENTAL MAHASISWA SEMESTER AKHIR UNIVERSITAS MUHAMMADIYAH PALOPO - Azis, Sri Bintang; Galugu, Nur Saqinah; Muhammad Irham Zainuri (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to examine the relationship between family pressure and the mental health of final-year students at Muhammadiyah University of Palopo. Students at the final stage of their studies are vulnerable to high levels of anxiety due to academic pressure, family expectations, and uncertainty about the future. This research employs a quantitative approach with a correlational method. The sample consisted of 300 final-year students selected using quota sampling techniques from four faculties. The instrument used was a Likert-scale questionnaire designed to measure two main variables: family pressure and anxiety, as indicators of mental health. The results of the validity and reliability tests indicate that the instrument is suitable for data collection. Data were analyzed using the Pearson Product Moment correlation technique. The findings reveal a positive and significant relationship between family pressure and students' anxiety levels (r = 0.466; p < 0.05). The higher the family pressure experienced by students, the higher their level of anxiety. This study concludes that family pressure is a crucial factor influencing the mental health of final-year students, particularly in the form of anxiety. Therefore, active involvement from families and educational institutions is necessary to provide emotional support so that students can complete their studies effectively and maintain psychological stability.